Community Perspectives of Complex Trauma Assessment for Aboriginal Parents: ‘Its Important, but How These Discussions Are Held Is Critical’ - Chamberlain, Catherine; Gee, Graham; Gartland, Deirdre; Mensah, Fiona K.; Mares, Sarah; Clark, Yvonne; Ralph, Naomi; Atkinson, Caroline; Hirvonen, Tanja; McLachlan, Helen; Edwards, Tahnia; Herrman, Helen; et al. (Frontiers in Psychology, 2020)
Background and purpose Becoming a parent can be an exciting and also challenging transition, particularly for parents who have experienced significant hurt in their own childhoods, and may be experiencing ‘complex trauma’. Aboriginal and Torres Strait Islander (Aboriginal) people also experience historical trauma. While the parenting transition is an important time to offer support for parents, it is essential to ensure that benefits of identifying parents experiencing complex trauma outweigh any risks (e.g. stigmatization). This paper describes views of predominantly Aboriginal stakeholders regarding (1) the relative importance of domains proposed for complex trauma assessment, and (2) how to conduct these sensitive discussions with Aboriginal parents. Setting and methods A co-design workshop was held in Alice Springs (Central Australia) as part of an Aboriginal-led community-based participatory action research project. Workshop participants were 57 predominantly Aboriginal stakeholders with expertise in community, clinical, policy and academic settings. Using story-telling and strategies to create safety for discussing complex and sensitive issues, and delphi-style methods, stakeholders rated the level of importance of 12 domains of complex trauma-related distress proposed based on existing assessment tools and community consultation; and discussed why, by whom, where and how experiences of complex trauma should be explored. Main findings The majority of stakeholders supported the importance of assessing each of the proposed complex trauma domains with Aboriginal parents. However, strong concerns were expressed regarding where, by whom and how this should occur. There was greater emphasis and consistency regarding ‘qualities’ (e.g. caring), rather than specific ‘attributes’ (e.g. clinician). Six critical overarching themes emerged: ensuring emotional and cultural safety; establishing relationships and trust; having capacity to respond appropriately and access support; incorporating less direct cultural communication methods (e.g. yarning, dadirri); using strengths-based approaches and offering choices to empower parents; and showing respect, caring and compassion. Conclusions Assessments to identify Aboriginal parents experiencing complex trauma should only be considered when the prerequisites of safety, trusting relationships, respect, compassion, adequate care and capacity to respond are assured. Offering choices and cultural and strengths-based approaches are also critical. Without this assurance, there are serious concerns that harms may outweigh any benefits for Aboriginal parents.